2019
DOI: 10.3390/jcm8020139
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Osseointegration and Mechanotransduction to Maintain Foreign Body Equilibrium in the Long-Term: A Comprehensive Overview

Abstract: The permanent interaction between bone tissue and the immune system shows us the complex biology of the tissue in which we insert oral implants. At the same time, new knowledge in relation to the interaction of materials and the host, reveals to us the true nature of osseointegration. So, to achieve clinical success or perhaps most importantly, to understand why we sometimes fail, the study of oral implantology should consider the following advice equally important: a correct clinical protocol, the study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 102 publications
(200 reference statements)
1
36
0
Order By: Relevance
“…Immune cells, including macrophages, T and B cells play a dually regulatory role in osteogenesis through a wide range of secreted cytokines in dose and time‐dependent pattern (Sadtler et al, 2016; Toben et al, 2011). Macrophages infiltrated into tissues induced by surgery trauma and response to titanium implant might express various functions for both promoting bone regeneration and mediating immune reaction to biomaterial (foreign body reaction) (Albrektsson et al, 2019; Amengual‐Penafiel et al, 2019), however, uneventful osseointegration of all implants have been achieved as usual as shown in the present study. The host immune response induced by implant installation did not have adverse effects on the formation of osseointegration despite CD68+ multinucleated giant cell formation at the bone‐to‐implant interface.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Immune cells, including macrophages, T and B cells play a dually regulatory role in osteogenesis through a wide range of secreted cytokines in dose and time‐dependent pattern (Sadtler et al, 2016; Toben et al, 2011). Macrophages infiltrated into tissues induced by surgery trauma and response to titanium implant might express various functions for both promoting bone regeneration and mediating immune reaction to biomaterial (foreign body reaction) (Albrektsson et al, 2019; Amengual‐Penafiel et al, 2019), however, uneventful osseointegration of all implants have been achieved as usual as shown in the present study. The host immune response induced by implant installation did not have adverse effects on the formation of osseointegration despite CD68+ multinucleated giant cell formation at the bone‐to‐implant interface.…”
Section: Discussionsupporting
confidence: 65%
“…Unlike the normal bone injury healing process, placement of a dental implant into the jaw bone may interfere with the healing process in some way and also influence bone regeneration (Amengual‐Penafiel et al, 2019). Donath has already revealed that different bone tissue reactions such as a bony demarcation or a fibrous encapsulation may develop around the biomaterials placed in bone tissue depended on several factors associated with the severity of the inflammatory response (Donath, Laass, & Gunzl, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Acute inflammation is initiated by the pro-inflammatory cytokines, including interleukin-6 and tumor necrosis factor-alpha, released by immune cells, as well as by osteoblasts and fibroblasts of surrounding tissues. However, the excessive release of pro-inflammatory cytokines indicates activation of chronic inflammation, which leads to a failure of osseointegration [ 36 ]. Therefore, the gene expression of the following pro-inflammatory cytokines was examined: interleukin-6 ( IL6 ) and tumor necrosis factor-alpha ( TNFA ) in osteoblast-like cells (SaOS-2) and fibroblast-like cells (3T3 cell line).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the foreign body response to differently reabsorbable materials, such as ceramics, is a great concern particularly in a compromised microenvironment, as in OP. When a prosthetic material is implanted, the process of osseointegration occurs through the establishment of the foreign body equilibrium [94] that has to be maintained as long as possible. Within bone, macrophages exert a pivotal role on one hand in driving the transition between the M1 inflammatory phenotype in the early reparative phase and the M2 anti-inflammatory phenotype in the later stages [94] and secondly being precursors of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%